Impact of conditioning intensity in T-replete haplo-identical stem cell transplantation for acute leukemia: a report from the acute leukemia working party of the EBMT. Issue 1 (December 2016) - Rubio, Marie; Savani, Bipin; Labopin, Myriam; Piemontese, Simona; Polge, Emmanuelle; Ciceri, Fabio; Bacigalupo, Andrea; Arcese, William; Koc, Yener; Beelen, Dietrich; Gülbas, Zafer; Wu, Depei; et al.
Abstract Background Increasing numbers of patients are receiving haplo-identical stem cell transplantation (haplo-SCT) for treatment of acute leukemia with reduced intensity (RIC) or myeloablative (MAC) conditioning regimens. The impact of conditioning intensity in haplo-SCT is unknown. Methods We performed a retrospective registry-based study comparing outcomes after T-replete haplo-SCT for patients with acute myeloid (AML) or lymphoid leukemia (ALL) after RIC (n = 271) and MAC (n = 425). Regimens were classified as MAC or RIC based on published criteria. Results A combination of post-transplant cyclophosphamide (PT-Cy) with one calcineurin inhibitor and mycophenolate mofetil (PT-Cy-based regimen) for graft-versus-host disease (GVHD) prophylaxis was used in 66 (25 %) patients in RIC and 125 (32 %) in MAC groups. Patients of RIC group were older and had been transplanted more recently and more frequently for AML with active disease at transplant. Percentage of engraftment (90 vs. 92 %;p = 0.58) and day 100 grade II to IV acute GVHD (24 vs. 29 %, p = 0.23) were not different between RIC and MAC groups. Multivariable analyses, run separately in AML and ALL, showed a trend toward higher relapse incidence with RIC in comparison to MAC in AML (hazard ratio (HR) 1.34, p = 0.09), and no difference in both AML and ALL in terms of non-relapse mortality (NRM) chronic GVHD and leukemia-free survival. There was no impact of conditioning regimen intensity in overall survival (OS) in AML (HR = 0.97, p = 0.79) but a trend for worse OS with RIC in ALL (HR = 1.44, p = 0.10). The main factor impacting outcomes was disease status at transplantation (HR ≥ 1.4, p ≤ 0.01). GVHD prophylaxis with PT-Cy-based regimen was independently associated with reduced NRM (HR 0.63, p = 0.02) without impact on relapse incidence (HR 0.99, p = 0.94). Conclusions These data suggest that T-replete haplo-SCT with both RIC and MAC, in particular associated with PT-Cy, are valid options in first line treatment of high risk AML or ALL.